A hódmezővásárhelyi országgyűlési képviselő-választások 1926-ban - Zeman, Ferenc (Közép-Európai Közlemények, 2013)
In the end of 1926 there was the general election in Hungary. The vote passed off by the new electoral law, which was made in 1925. In the city of Hódmezıvásárhely the election – which was secret and made with partylists – was held from 12 to 13 december. In the course of the campaign three parties managed to have the enough recommendations the Independence Party (with the leadership of Béla Kun), the Unit Party (with János Mayer agricultural minister) and the Hungarian Socialdemocrat Party (with the leadership of Ferenc Szeder). The recommendation threshold was 10 percent of the number of all constituent. (1127 people). In the course of the campaign all of the parties attacked each other, and they promised a lot. The winner of the election was the Independence Party, the second place was owned by the party of the government. The parliamentarian of the city become Béla Kun and János Mayer.